2016
DOI: 10.1039/c5dt03914b
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in assignment of orbital populations in a high spin manganese(iii) complex

Abstract: Magnetic, structural and computational data of four complex salts with the same mononuclear high spin octahedral Mn(iii) complex cation are reported. The manifestation of Jahn-Teller-like distortions in the Mn(iii) cation is dependent on the nature of the charge-balancing anion, with small anions yielding a planar elongation and large anions freezing out a preferential axial elongation along one of the amine-Mn-imine directions within that same plane. Modulation of the lattice by changing the charge balancing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 53 publications
0
8
1
Order By: Relevance
“…The HOMO and LUMO orbitals of the two Mn(III) complexes were found to be very similar. Computational studies suggested that the geometry of the ligand does not prevent the possibility of SCO, contrary to what was found for the Morgan systems [73,74]. 5 Complexes, HS (S = 5/2) and LS (S = 1/2)-Fe(III)…”
Section: Results Solid Statecontrasting
confidence: 65%
“…The HOMO and LUMO orbitals of the two Mn(III) complexes were found to be very similar. Computational studies suggested that the geometry of the ligand does not prevent the possibility of SCO, contrary to what was found for the Morgan systems [73,74]. 5 Complexes, HS (S = 5/2) and LS (S = 1/2)-Fe(III)…”
Section: Results Solid Statecontrasting
confidence: 65%
“…They are close to the values observed in the [Mn(3,5-diBr-sal-N-1,5,8,12)] + BPh 4 À complex at 250 K. [19] The bond angles XÀ Mn-X deviate from ideal 90/180 °values showing significant distortion of the Mn III N 4 O 2 octahedron typical for the HS state. The octahedral distortion parameters (Σ, Θ and ζ) calculated using the OctaDist [4,23] tool are listed in Table 1.…”
Section: Crystal Structuresmentioning
confidence: 99%
“…Octahedral distortion parameters were calculated within OctaDist software. [23] The powder XRD patterns for 1-3 were recorded at room temperature on an Aeris diffractometer (Malvern PANalytical B.V., Netherlands). The powder XRD measurements showed that all polycrystalline samples 1-3 are monophase crystalline materials corresponding to the single crystal data (Figure S1).…”
Section: X-ray Crystallographymentioning
confidence: 99%
“…In recent years, noncovalent interactions, such asstacking and hydrogen bonding, have been shown to be a new channel for magnetic exchange in supramolecular chemistry (Fukuroi et al, 2014;Hicks et al, 2001;Atzori et al, 2014;Fitzpatrick et al, 2016). [Fe(HL) 2 Cl 4 ] (L is 2-aminopyrazine) is a discrete complex having a 2D layer structure formed by halogen bonding between Cl and the N atom of the amine substituent on the pyrazine moiety of an adjacent complex.…”
Section: Propagation Of Magnetic Interactions Through Hydrogen Bondingmentioning
confidence: 99%